Sacitra Anuyogadvāra sūtra: mūla śuddha pāṭha, hindī-aṅgrejī anuvāda, vivecana tathā raṅgīna citroṃ sahita = Illustrated Anuyogadvar sutra : original text with Hindi and English translations, elaboration and multicoloured illustrations - Amaramuni; Surānā, Śrīcanda, Sarasa; Bothara, Surendra (Prakrit Bharti pushp 226, 2001)
Jaina canonical text